Key findings of IEA EBC Annex 68 - indoor air quality design and control in low energy residential buildings. Issue 3 (September 2019) - Rode, C; Abadie, M; Qin, M; Grunewald, J; Kolarik, J; Laverge, J
Abstract: The overall objective of the "Annex 68" Project, which belongs to the International Energy Agency's "Energy in Buildings and Communities" Implementing Agreement, has been to develop the fundamental basis for optimal design and control strategies for good Indoor Air Quality (IAQ) in highly energy efficient residential buildings, and to disseminate this information in a practically applicable guide. The strategies shall facilitate the possibility to design and operate residential buildings with minimal energy use, while ensuring impeccable indoor climates. The project completes its working phase by the end of spring 2019. The work has gathered laboratory and field data and developed new knowledge on pollution sources in buildings and how the transport mechanisms for the pollutants interact with heat, air and moisture conditions in materials and indoor zones. Furthermore, the project has assembled a set of contemporary models to simulate the combined heat, air, moisture and pollution conditions of buildings and their assemblies. The purpose has been to identify and describe amenable ways to optimize the provision of ventilation and air-conditioning. The paper gives an account of the project highlights.